Sistem Pakar untuk Mendiagnosa Penyakit Hati Menggunakan Metode Forward Chaining - Prista Amanda Putri; Hindayati Mustafidah (JUITA : Jurnal Informatika, 2011)
Requirement for rapid and precise information from a medical specialist in internal medicine is required. This has encouraged the development of an expert system application for liver disease is made. Expert system for diagnosing liver diseases was designed as a tool for diagnosing liver disease with knowledge base. Knowledge base obtained from several sources, is through interviews and books. This expert system used development method is problem identification, design, system design, coding, testing and implementation. Knowledge base compiled into a database with multiple tables. As the main table is diagnosis table or conclusion. Inference in an expert system uses a forward chaining method. The programming language used JSP (Java Server Pages), as for database uses SQL Server database. This expert system will show a selection of symptoms, which every symptoms would lead to a further choice  to get the symptoms of the illness conclusions, solutions and explanations